Fabrication and Characterization of Metformin, Gentamicin and Curcumin Loaded Hydrogel for Wound Healing - Nimra, Mehak; Afzal, Fahad (International Pharmacy Acta, 2024)
Chitosan is a sugar derived naturally and used in medicine for its different uses, like wound dressings, drug delivery systems, medical implants, and hydrogels. This study fabricated a chitosan hydrogel loaded with curcumin, gentamicin, and metformin. The physical properties included swelling index, tensile strength, elongation profile, and drug release. The chitosan hydrogel is used to treat burn wounds and boost the healing process in Wistar rats. The chitosan hydrogel showed bonding with acetate, and after the formation of chitosan acetate, the pH was raised using sodium hydroxide to achieve cross-linking using formaldehyde and tween 80. The hydrogel characterization showed all the peaks and parameters that ensured the fabrication of drug-loaded chitosan hydrogel. The physical properties revealed increased tensile strength and elongation percentage with increased chitosan concentration. At the same time, there was a negative effect on the porosity and water adsorption. The best tensile strength and elongation percent were shown at 1.2 grams of chitosan, 0.32 Mpa, and 62 percent, respectively. Scanning electron microscopy showed that the pore sizes were 50±2 µm. The surface showed drug loading, which is the reason the drug was released initially as a burst and then uniform. When compared to the control group, the in vivo study found that the drug-loaded chitosan and chitosan hydrogel improved wound healing. Compared to the control group, there was an increased formation of collagen, rete ridges, epidermal bed length, and scar formation in the chitosan and drug-loaded chitosan groups. The best wound closure was seen in the drug-loaded chitosan group, which was 12.5% wound size by the end of the 3rd week. Using chitosan alone can accelerate burn wound healing, and the lower wound PH in the respective group also showed this. However, certain drugs could boost wound healing even more, as showcased in this study. Drug-loaded hydrogel wound dressings could revolutionize the wound-healing process.